Tenecteplase: biochemical and clot lysis activity comparisons - Bechmann, Jan; Schmid, Ira; Brand, Simone; Miller, Felix; Zhang, Chengzhi (Frontiers in Pharmacology, 2024)
Introduction In the last decades, the recombinant tissue plasminogen activator alteplase has been the standard fibrinolytic treatment of acute myocardial infarction, pulmonary embolism, and acute ischemic stroke. An optimized version of alteplase, tenecteplase, has been developed by exchanging six amino acids to increase half-life, achieve higher fibrin selectivity and increase resistance to plasminogen activator inhibitor-1. Meanwhile, several products containing tenecteplase exist. The aim of this study was to compare the fibrinolytic activity and overall product quality of the 25 mg/vial presentation of tenecteplase originator Metalyse® (Boehringer Ingelheim Pharma GmbH and Co., KG, Ingelheim, Germany) to the 16 mg/vial formulation of the tenecteplase copy Mingfule® (CSPC Recomgen Pharmaceutical, Guangzhou, Co., Ltd.). Methods We have systematically analyzed and evaluated the biochemical and fibrinolytic differences between Metalyse® and Mingfule® using a wide range of routine quality testing assays, supplemented by mass spectrometry analysis and surface plasmon resonance assays. Additional host cell protein quantification and clot lysis testing following plasmin incubation over time were performed. Results Several key differences in biochemical composition and clot lysis activity were observed between the two tenecteplase variants. Versus Metalyse®, Mingfule® exhibited lower clot lysis activity and contained less of the two-chain form of tenecteplase. In addition, there were differences in sialic acid content, galactosylation, and fucosylation patterns, with Mingfule® exhibiting more bi- and less tri- and tetra-antennary glycosylation, leading to a different charge and size heterogeneity profile. Furthermore, Mingfule® displayed highly dissimilar binding to the three clearance receptors (LRP-1, ASGR, and mannose receptor) compared with Metalyse®. Purity analysis showed that Mingfule® contained a lower monomer content and, in contrast to Metalyse®, substantial amounts of host cell protein. Discussion Taken together, these data demonstrate that the tenecteplase copy Mingfule® has several meaningful fibrinolytic and biochemical differences compared with Metalyse®. This raises the question of whether data from clinical studies with one of the products can be generalized for all tenecteplase variants.